ANALISIS PEMBELAJARAN ADAB PROJECT SEBAGAI SARANA PENGUASAAN KEMAMPUAN KOLABORASI SISWA SDN 7 PEMENANG BARAT TAHUN AJARAN 2023/ 2024 - Sapoandi , Muhamad; Hadiyaturrido; Marzoan (Lembaga Bale Literasi, 2024)
This study aims to analyze ADAB Project learning as a means of mastering the collaboration skills of students of SDN 7 Juara Barat for the 2023/2024 academic year. This research was carried out in grade 4 of SDN 7 Juara Barat with a total of 23 students. This study uses qualitative research with a case study approach, data collection techniques are carried out by means of observation, interviews and documentation. Data sources were obtained from school principals, classroom teachers and students of SDN 7 Juara Barat. The data analysis technique in this study was carried out in three stages, namely 1) data condensation, 2) data display, and 3) conclusion drawing or verification, while the validity of the data was verified through triangulation techniques and source triangulation. Berdasarkan hasil penelitian bahwa dalam proses pembelajaran, ada 3 tahapan yang dilakukan oleh guru yaitu Tahap perencanaan, pelaksnanaan dan evaluasi. Pada Tahap perencanaan meliputi menentukan materi pembelajaran yang akan di ADAB Project-kan, mengkaji karaktristik siswa, Menyusun rancangan pelaksanaan pembelajaran ADAB Project (RPP ADAB Project), merumuskan tujuan pembelajaran, menentukan jadwal pelaksanaan pembelajaran ADAB Project, menyiapkan sumber belajar dan lembar kerja siswa (LKPD) dan Menyusun alat penilaian/evaluasi. Pada Tahap pelaksanaan ialah penerapan pembelajaran ADAB Project sesuai dengan tahapan-tahapan pembelajaran ADAB Project. There are four stages of the ADAB Project, namely asking questions, assisting with investigations, inviting work and sharing results. Meanwhile, at the evaluation stage, teachers conduct assessments, the aspects that are assessed are attitudes and products. The supporting factors for ADAB Project learning include teachers' ability to implement ADAB Project learning, student enthusiasm, adequate facilities, and the availability of learning resources. Meanwhile, the inhibiting factors for learning the ADAB Project come from students, namely 4th grade students who are still in the transition stage from low to high grades, so they need more control so that the classroom atmosphere remains conducive. In addition, the inhibiting factor for the implementation of ADAB Project learning is time limitations and requires costs. As for the impact of ADAB Project learning on students' collaboration skills, ADAB Project learning can improve and develop students' collaboration skills, this can be seen from students' ability to work together, responsibility to complete projects, ability to establish communication and ability to make agreements through compromise, overall these skills are very good.